THE INFLUENCE OF USING AUDIO-VISUAL METHOD AND LISTENING ATTITUDE TOWARDS THE LISTENING ABILITY AT THE SECOND LEVEL CADETS OF D III LALU LINTAS ANGKUTAN SUNGAI DANAU DAN PENYEBERANGAN (LLASDP) PALEMBANG - Tahrun Tahrun; Rita Inderawati; Oktrianti Diani (ELTE Journal (English Languange Teaching and Education), 2017)
This study investigated to find out whether or not there were any significant differences of the second level cadets’ listening ability and listening attitude  using audio-visual method (video materials). By using questionnaire forty cadets were selected as the sample and equally divided into experimental and control groups. By applying pretest and posttest control group design the treatment was only given to the experimental group. The data were analyzed by using three techniques: they were the statistical analysis on measuring homogenity and normality data, independent t-test, and two-way ANOVA. Due to the research findings, it was found that (1) there was significant difference in listening ability between positive and negative attitude students who were taught by using Video materials (0.000<0.05). (2) there was significant difference in listening ability between positive and negative attitude students who were taught by using conventional technique (0.000<0.05). (3) there was significance difference in listening ability between positive and negative attitude students who were taught by using video materials and those who were taught by using conventional technique (0.000<0.05). (4) there was a significant interaction effect of Video materials and listening attitude towards the listening ability at the second level cadets of D III Lalu Lintas Angkutan Sungai Danau dan Penyeberangan (LLASDP) Palembang (0.020 < 0.05).Keywords: video materials, listening attitude, and listening ability